(untitled) (Devenires, 2013)
The transmission of scientific knowledge of the Hellenic world, especially philosophical Greek thought into the Islamic world, represents a key moment in scientific and philosophical thought history. Al-Kindī among Muslim philosophers marks a transition phase that goes through a simply reception to a creation of a philosophical thought, with an appropriate conceptual tool in Arabic language. In this sense, al-Kindī analyzed and commented different texts of Greek philosophical tradition, creating in the Islamic world thought dedicated to development of philosophy and scientific disciplines. The main purpose of this paper is expose some relevant aspects of al-Kindī thought, the Philosopher of the Arabs, particularly, the relationship between philosophy (reason) and religion (faith), the classification of philosophical knowledge, and the soul and intellect theory. Al-Kindī’s approach on these themes is a decisive moment in the development of philosophy in the Islamic world.